1975
DOI: 10.1111/j.1600-0714.1975.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry of the keratohyalin granules in human oral leukoplakia

Abstract: The keratohyalin granules from 25 human oral leukoplakias, showing benign hyperorthokeratosis histologically, were examined employing a series of histochemical techniques. The tissues were fixed in 10% neutral buffered formalin, 80% methanol, or Carnoy's fluid. The keratohyalin granules stained intensely with Pauly's reagent, Congo red and Harris hematoxylin, indicating the presence of proteins. This was confirmed by abolishing the staining reaction by pretreatment with proteolytic enzymes. The keratohyalin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In contrast, however, the typically described keratohyalin granules stain intensely with Harris' hematoxylin [Ugel, 1971 ;Singh et al, 1975] thus impart ing a basophilic appearance. On the other hand, analysis of correlative data from vari ous laboratories employing histochemical, autoradiographic, ultrastructural and biochemical methods have indicated that the basophilic keratohyalin granules from epithelium of oral mucosa and skin are ultrastructurally heterogeneous and also vary in their biological composition [Farbman, 1966a;Sibrack et al, 1974;Matoltsy et al, 1974;Fukuyama and Epstein, 1975;Singh et al, 1976].…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, however, the typically described keratohyalin granules stain intensely with Harris' hematoxylin [Ugel, 1971 ;Singh et al, 1975] thus impart ing a basophilic appearance. On the other hand, analysis of correlative data from vari ous laboratories employing histochemical, autoradiographic, ultrastructural and biochemical methods have indicated that the basophilic keratohyalin granules from epithelium of oral mucosa and skin are ultrastructurally heterogeneous and also vary in their biological composition [Farbman, 1966a;Sibrack et al, 1974;Matoltsy et al, 1974;Fukuyama and Epstein, 1975;Singh et al, 1976].…”
Section: Discussionmentioning
confidence: 89%
“…Similar keratohyalin granules are found in masticatory mucosae but, additionally, in both masticatory and lining mucosae, there are keratohyalin granules of spherical shape in association with ribosomes but not, apparently, with tonofilaments; within any particular cell, one type of granule tends to prevail (Jessen 1970, Schroeder 1981. Regional variation in the composition of oral keartohyalin has also been demonstrated by histochemical methods (Singh et al 1975(Singh et al , 1980.…”
Section: Ultrastructural Findingsmentioning
confidence: 93%